-3
No. 4 is the square root of 4 squared. 3 is the square root of 3 squared.That's not what I meant. It is worded like this. 4 √3².- well the square root of three * 3 is 3, so then 3*4 is 12. There you have it folks, real hard...
16 root 24
The cube root of 4 to the power of 3 is the same as the cube root of 64, which equals 4. This is because raising a number to the power of 3 and then taking the cube root of that result cancels out the exponentiation. In this case, 4 cubed is 64, and the cube root of 64 is 4.
hmm... okay, if I understand you correctly, 2 times the square root of 3 times the square root of 12? = 2(1.73)(3.46) = 11.9716. If you aren't using the approximations, then just simplifying is... [sorry, I can't do the square root sign on the computer...] 2(square root of 3)(square root of 12) = 2(square root of 3)(square root of 4*3) = 4(square root of 3)(square root of 3) = 4(3) = 12!!! HOPE I HELPED!! :-)
4 square root 3 + 4 cube root 3 is 12.6972015
-3
No. 4 is the square root of 4 squared. 3 is the square root of 3 squared.That's not what I meant. It is worded like this. 4 √3².- well the square root of three * 3 is 3, so then 3*4 is 12. There you have it folks, real hard...
16 root 24
1.4142135 is the square root of 2 1.7320508 is the square root of 3 2.0000000 is the square root of 4
Surds are based on roots. Root 8 can be split into root 4 and root 2; as there's a root to 4, get that number, and multiply it by the remaining root. So root 8 = 2 root 2. Root 40 would be 2 root 10 Root 48 would be root 4, root 4, root 3 Root 48 = 4 root 3.
3*3=9 and 4*4=16. Therefore the square root of 13 is closer to 4 than to 3.
(4/4)-(the square root of 4)-(the square root of 4)
No, it is not. Root 12 = root 4 * root 3, which is the same as 2*root 3. And you should already know than root 3 is irrational.
sqrt(4) = 2 sqrt(9) = 3 Therefore, the square root of 4 plus the square root of 9 is equal to 2 + 3 = 5.
10 square root 3.
3